Salt in the Wound : Encountering Contemporary Artists across Europe - Benschop, Jurriaan (Helsinki : Garret Publications, 2019)
Encountering Contemporary Artists : Avotins, Jãnis ; Batka, Mirostaw ; Bisky, Norbert ; Borremans, Michaël ; Botea, Irina ; Frize, Bernard ; Henning, Anton ; Kameric, Sejla ; Kapoor, Anish ; Kasearu, Flo et al.
Salt in the Wound takes the reader on a journey through Europe, to meet with artist and talk about their work, their environment and artistic roots. Through studio visits, exhibition reviews and conversations, the author reflects on the imagination of leading European artists, and how it relates to both local histories and the global art practice.(from the webside of the author)
boek